Cyber sex menurut perspektif hukum islam dan undang-undang no. 44 tahun 2008 tentang pornografi - Fawwas .; Achmad . (STAI Syaichona Moh. Cholil Bangkalan, 2019)
Pornography is an old problem that cannot be addressed by the provisions contained in the Criminal Code (Wetbook van Starvrecht Nederlandsch-Indie). The negative impact of pornography is increasingly worrisome, including: the occurrence of rape, adultery and abortion. Then the Indonesian Ulema Council (MUI) issued a fatwa Number 287 of 2001 concerning the prohibition against pornography and porno-action, because it was guided by the law on the many disadvantages of the benefits arising from pornography and porno-action and the prohibition against acts of approaching adultery. Because pornography and porno-action can be closer to adultery. In Islam also recognizes freedom of expression and opinion, does not mean freedom is used for negative purposes such as pornography and porno-action. But freedom of expression and opinion must be accountable not only to humans but also to Allah SWT. Islam teaches that the main purpose of life and human life is to get the pleasure of Allah alone. And accountable for all his actions while living in the world, including treating and utilizing his body as a mandate of Allah SWT.